Al-Quran learning using mobile speech recognition:an overview - Kamarudin, Noraziahtulhidayu; Syed Mohamed, Syed Abdul Rahman Al-Haddad; Hassan, Abd Rauf; Abushariah, Mohammad A. M. (IEEE, 2014)
The usage of mobile application in various aspects has been worldwide accepted and there are variety of mobile applications which developed to cater the usage of different background of the user. In this paper, a short survey which includes questionnaire is distributed to find the interest of user whom using application for learning Quran and concept of mobile speech apps. The main interest of this survey is to find the acceptance of user and explanation on the proposed usage of mobile speech recognition with feature of learning apps. Factors of mobile speech recognition and mobile learning are listed to support the results from the short survey.